Pengaruh Likuiditas, Solvabilitas Dan Aktivitas Terhadap Kinerja Keuangan Perusahaan Sektor Energi Yang Terdaftar Di Indeks LQ45 Pariode 2019 – 2023 - Santoso, Wawan; Saputra, Irwan Adimas Ganda (Jurnal Publikasi Ekonomi dan Akuntansi, 2026)
This study aims to analyze the effect of liquidity, solvency, and activity ratios on the financial performance of energy sector companies listed in the LQ45 index during the 2019–2023 period. The independent variables used are the Current Ratio (CR) as a measure of liquidity, the Debt to Equity Ratio (DER) as a measure of solvency, and the Account Receivable Turnover (ARTO) as a measure of activity. Financial performance is measured using Return on Assets (ROA). This research employs a descriptive quantitative approach with purposive sampling, focusing on four energy companies consistently listed in the LQ45 index for five consecutive years. Data analysis was conducted using multiple linear regression with the assistance of SPSS software. The results show that partially, the current ratio and account receivable turnover have a significant effect on ROA, while the debt to equity ratio has no significant effect. Simultaneously, the three financial ratios have a significant effect on financial performance. These findings provide important implications for company management, investors, and academics in making decisions related to financial efficiency in the energy sector.